Identifying essential implementation strategies: a mixed methods process evaluation of a multi-strategy policy implementation intervention for schools - Cassandra Lane; Patti-Jean Naylor; Adam Shoesmith; Luke Wolfenden; Alix Hall; Rachel Sutherland; Nicole Nathan (BMC, 2022)
Abstract Background Physically Active Children in Education (PACE) is composed of eight implementation strategies that improves schools' implementation of a government physical activity policy. A greater understanding of each discrete implementation strategy could inform improvements to PACE for delivery at-scale. This study aimed to: (A) measure the dose delivered, fidelity, adoption and acceptability of each strategy using quantitative data; (B) identify implementation barriers and facilitators using qualitative data; and (C) explore the importance of each strategy by integrating both data sets (mixed methods). Methods This study used data from a cluster randomised noninferiority trial comparing PACE with an adapted version (Adapted PACE) that was delivered with reduced in-person external support to reduce costs and increase scalability. Data were collected from both trials arms for between-group comparison. Descriptive statistics were produced using surveys of principals, in-school champions and teachers; and project records maintained by PACE project officers (objective A). Thematic analysis was performed using in-school champion and project officer interviews (objective B). Both data sets were integrated via a triangulation protocol and findings synthesized in the form of meta-inferences (objective C). Results Eleven in-school champions and six project officers completed interviews; 33 principals, 51 in-school champions and 260 teachers completed surveys. Regardless of group allocation, implementation indicators were high for at least one component of each strategy: dose delivered =100%, fidelity ≥95%, adoption ≥83%, acceptability ≥50%; and several implementation barriers and facilitators were identified within three broad categories: external policy landscape, inner organizational structure/context of schools, and intervention characteristics and processes. All strategies were considered important as use varied by school, however support from a school executive and in-school champions' interest were suggested as especially important for optimal implementation. Conclusion This study highlights the importance of both executive support and in-school champions for successful implementation of school physical activity policies. In particular, identifying and supporting an in-school champion to have high power and high interest is recommended for future implementation strategies. This may reduce the need for intensive external support, thus improving intervention scalability.